Dissecting the Biology of the Fungal Wheat Pathogen Zymoseptoria tritici: A Laboratory Workflow. Issue 1 (11th November 2020) - Fagundes, Wagner C.; Haueisen, Janine; Stukenbrock, Eva H.
Abstract: The fungus Zymoseptoria tritici is one of the most devastating pathogens of wheat. Aside from its importance as a disease‐causing agent, this species has emerged as a powerful model system for evolutionary genetic studies of crop‐infecting fungal pathogens. Z. tritici exhibits exceptionally high levels of genetic and phenotypic diversity as well as morphological plasticity, which can make experimental studies and comparability of results obtained in different laboratories, e.g., from infection assays, challenging. Therefore, standardized experimental methods are crucial for research on Z. tritici biology and the interaction of this fungus with its wheat host. Here, we describe a suite of well‐tested and optimized protocols ranging from isolation of Z. tritici field specimens to analyses of virulence assays under controlled conditions. Several biological and technical aspects of working with Z. tritici under laboratory conditions are considered and carefully described in each protocol. © 2020 The Authors. Basic Protocol 1 : Purification of Z. tritici field isolates from leaf material Basic Protocol 2 : Molecular identification of Z. tritici isolates Support Protocol 1 : Rapid extraction of Z. tritici genomic DNA Support Protocol 2 : Extraction of high‐quality Z. tritici genomic DNA Basic Protocol 3 : In vitro culture and long‐term storage of Z. tritici isolates Basic Protocol 4 : Analysis of Z. tritici virulence in wheat Support Protocol 3 : Preparation of Z. tritici inoculum